(untitled) (Research, Society and Development, 2020)
This study aimed to evaluate genipap seedling formation in different protected environments using different substrates. Five protected cultivation environments (E) were used: E1 - greenhouse without aluminized shade cover under polyethylene film; E2 - greenhouse with aluminized shade cover under polyethylene film; E3 - screened with black shade cover; E4 - screened with aluminized shade cover; and E5 - nursery covered with bacuri coconut straw. In each protected cultivation environment, substrates containing different percentages of earthworm humus (H), vermiculite (V), bovine manure (M) and shredded cassava stems (C) were tested. Seedlings emerged best in environments E2, E3 and E4. Mixtures ¾ H + ¼ V and ¾ H + ¼ C favored growth and yielded high quality seedlings. Environments E3 and E4 provided superior growth, with better- quality and high-quality seedlings. Environments E1 and E5 did not provide adequate seedling growth. Therefore, were not recommended for genipap seedling production using the substrates tested.